Two New Species of Salamanders, Genus Bolitoglossa (Amphibia: Plethodontidae), from the Eastern Colombian Andes - Acevedo, Aldemar A.; Wake, David B.; Márquez, Roberto; Silva, Karen; Franco, Rosmery; Amézquita, Adolfo (Zootaxa, 2013)
The salamander fauna of Colombia is very poorly known, probably because most research efforts have been devoted to anurans during the last two decades. Here, we describe two new species of the genus Bolitoglossa (Eladinea) from the eastern flank of the Eastern Colombian Andes (Cordillera Oriental), near the border with Venezuela. Bolitoglossa tamaense sp. nov. is distributed between 2000 to 2700 m.a.s.l. and Bolitoglossa leandrae sp. nov. is distributed in the low-lands at about 600 m. The new species are diagnosed by a combination of molecular (16S rRNA sequences), coloration, body size, and morphometric (number of maxillary and vomerine teeth and differences in foot webbing) characters. Both species face threats such as chytridiomycosis infections and habitat fragmentation that have already affected other sala-manders in the country. Thus, intensive field and museum work is needed to better document and perhaps protect the local salamander diversity.